ASPEK HUKUM MENGENAI GANTI KERUGIAN DALAM HAL TERJADINYA PERBUATAN MELAWAN HUKUM - , Muhammad Syah Rizky Perdana Putra ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research purposes this is to know form losses the result of illegal actions in its scope kuh.perdata and to know judicial consideration loss immateriil can sued by parties who were cheated based on the regulation. Rules referred to is provision in kuh.perdata, and any rules Research writer use in drafting this thesis is that research is juridical normative. Research is juridical normative research the principle law, referring to systematics law and justice as the normative and legal research based on research documentary liberary to obtain data in the field of law, secondary relevant to legal aspects concerning restitution in respect of the occurrence of an unlawful act, to answer the problems have been formulated. To furnish data secondary and also performed library research. The research found that the first losses and form elements, in tort including two major topics, namely in tort resulting losses on loss form of tort, indemnity Arrangements in KUH.Civil liability and tort, indemnity in KUH.The civil code, as for the elements of the tort, among others, is there an Act, deed against the law of nature, there are errors performers that consist of any deliberate action item, there are elements of negligence (ingebrekenstelling), there is no reason or excuse pembenar forgiving (rechtvaardigingsgrond), such as the State, self defence, overmacht mechanism of the soul, as well as any losses suffered casualties, there are causal relationships between the deed with a loss, loss due to form of the tort is the nominal indemnitycompensation, damages, punitive damages. Second, the immateril of damages in tort measure of damages in tort, immateril form of immateril due to damages in tort, the basic consideration of damages immateril i.e. immateril is associated with mental distress, associated with impending losses, damages can be claimed by immateril the party aggrieved, as well as damages as a means of legal protection